Lancret-type theorems in equiaffine space - Ogrenmis, Meltem; Ogrenmis, Alper Osman (Springer Basel Ag, 2024)
In this study we first introduce the notion of general helix in an equiaffine 3-space by the property that a fixed direction, called axis always, lies in the rectifying plane. We prove a Lancret-type theorem for equiaffine general helices. Using a similar argument, we also define equiaffine slant helices and classify them.
Keywords: Lancret's Theorem; General helix; Slant helix; Equiaffine space